2011
DOI: 10.1007/s00442-011-2139-1
|View full text |Cite
|
Sign up to set email alerts
|

Atmospheric change alters foliar quality of host trees and performance of two outbreak insect species

Abstract: This study examined the independent and interactive effects of elevated carbon dioxide (CO(2)) and ozone (O(3)) on the foliar quality of two deciduous trees species and the performance of two outbreak herbivore species. Trembling aspen (Populus tremuloides) and paper birch (Betula papyrifera) were grown at the Aspen FACE research site in northern Wisconsin, USA, under four combinations of ambient and elevated CO(2) and O(3). We measured the effects of elevated CO(2) and O(3) on aspen and birch phytochemistry a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
29
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 47 publications
(31 citation statements)
references
References 66 publications
1
29
1
Order By: Relevance
“…Furthermore, by influencing the chemical composition of senesced litter that fuels the metabolism of soil heterotrophs, the climate-induced physiological alterations in plants could also influence soil nutrient cycling and ecosystem productivity. For example, climate-induced changes in the composition of senescing leaves (Top and Filley, 2014; Suseela et al, 2015) could affect the subsequent detritivory (Currano et al, 2008; Couture et al, 2012) that regulates the cycling of soil carbon and mineral nutrients (Aerts, 1997; Liu et al, 2009; Suseela et al, 2013), which in turn could influence ecosystem productivity. These protracted influences of environmental stress on ecosystem performance could be mediated in part by climatic regulation of defense compounds that retain their biological-inhibitory properties even after tissue senescence.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, by influencing the chemical composition of senesced litter that fuels the metabolism of soil heterotrophs, the climate-induced physiological alterations in plants could also influence soil nutrient cycling and ecosystem productivity. For example, climate-induced changes in the composition of senescing leaves (Top and Filley, 2014; Suseela et al, 2015) could affect the subsequent detritivory (Currano et al, 2008; Couture et al, 2012) that regulates the cycling of soil carbon and mineral nutrients (Aerts, 1997; Liu et al, 2009; Suseela et al, 2013), which in turn could influence ecosystem productivity. These protracted influences of environmental stress on ecosystem performance could be mediated in part by climatic regulation of defense compounds that retain their biological-inhibitory properties even after tissue senescence.…”
Section: Introductionmentioning
confidence: 99%
“…single instar) performance of gypsy moths (Couture et al, 2012); in this study we examined effects of these gases on the long-term performance (survivorship, development time, pupal weight, and fecundity). Recent findings from this site have shown that aspen and birch exposed to elevated CO 2 and O 3 alter the short-term (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…This is positively correlated with the digestibility of the diet as well (Irwin et al 1993). Increased C:N ratio due to reductions in the concentrations of N and increases in structural carbohydrates lead to foliar quality decrease (Couture et al 2012).…”
Section: Introductionmentioning
confidence: 99%